Winning teams need both Diego Maradona and Franz Beckenbauer - Carlsson-Wall, M. (2020)
In this article, Martin Carlsson-Wall argues that organizations can become winners after COVID-19 by broadening their view of creativity and changing how they make decisions. Winning teams accept tensions and conflicts because the creative friction makes them grow and excel. A model is introduced with concrete steps for how this paradoxical decision-making can be achieved.